Trazos metodológicos en las investigaciones de Michel Foucault (2013)
ABSTARCT: This article approaches the issue of method in Michel Foucault's work. It was found that the object of his research has been the subject and the different forms of subjectification of human being in western culture. A series of elements have been found which make possible differentiating the historical and critical work of Foucault regarding classic history, the history of ideas, the history of sciences, and historical presentism. We conclude that, for implementing his method, Foucault: (1) performs three new positionings [present instead of actuality; beginning instead of origin, and founding instead of foundation], (2) favors the study of practices and (3) adopts two methodological tools that make his studies feasible: the procedures of eventualization and problematization.